The most common oral associations for senior students - Vaišvilaitė, V. (Psichologija, 1987)
The article presents the association responses provided by 500 senior Lithuanian students. The stimuli - words from Kent and Rosanoff’s list. Syntagmatic responses dominated.
Keywords: associations; senior students